Towards developing service quality index for zakat institutions - Abd. Wahab, Norazlina; Zainol, Zairy; Abu Bakar, Mahyuddin (Emerald Publishing Limited, 2017)
Purpose: This paper aims to present a conceptual model on service quality of zakat institutions that are responsible for collecting, managing and distributing zakat in Malaysia. Zakat is an Islamic religious “tax” charged on the rich and well-to-do members of the community for distribution to the poor and the needy as well as other beneficiaries based on certain established criteria according to the Qur’an. The main aim of zakat is to protect the socio-economic welfare of the poor and the needy.Design/methodology/approach: The paper reviews and synthesizes the relevant literature on service quality. The paper then proposed a conceptual model to study the service quality of zakat institutions.Findings: The paper identifies the appropriate methods to examine the extent of service quality of zakat institutions. Such evaluations are crucial for organizations like zakat institutions to function effectively to achieve the noble objectives of socio-economic justice through proper distribution of wealth.Originality/value: This paper presents a conceptual model of service quality of zakat institutions which would be useful for further empirical research in this area. The findings are not only relevant and applicable to Malaysia but also to other Muslim countries.